Unveiling motivational dynamics: a case study of young adult learners - Hamzah, Lina Mursyidah; Sueb, Rosilawati; Alias, Nurul Fitriah; Mustafa, Sharifah Muzlia Syed; Mohd Yusof, Mohammad Mubarrak (Research and Innovation Division, Universiti Teknologi MARA (UiTM) Selangor, 2025)
This study aims to delve into the motivational factors influencing learning among young adult learners in selected schools in Kuala Selangor, Malaysia. Utilizing a qualitative approach, four focus group discussions were conducted through semi-structured interviews with participants selected based on their exposure to motivational sessions organized by the researchers. Thematic analysis was employed to distil key insights from the gathered data, revealing six overarching themes. The identified themes encompass the reasons for attending school, the cultivation of interest in schooling, manifestations of disinterest in schooling, preferences for specific subjects, deliberate efforts to enhance academic performance, and the multifaceted factors contributing to academic achievement. Notably, the findings underscore that while teachers and peer influences can serve as motivating factors driving learners to attend school, these same factors may also pose challenges that impact overall success or failure. Given the transitional phase of young adult learners, characterized by ongoing cognitive development and physiological changes, educators and policymakers are urged to take a proactive stance. Specifically, interventions should be designed to foster motivation among young adult learners, especially those at risk of discontinuing their secondary education. This study emphasizes the nuanced interplay of motivational factors in the educational journey of young adults, urging a comprehensive and tailored approach to support their academic endeavours.